Особливості джерел викликаної активності кори головного мозку в лівшів та правшів під час класифікації стимулів, пов’язаних із локалізацією та формою об’єкта - Качинська, Тетяна; Абрамчук, Ольга; Кузнєцов, Ілля; Kachynska, Tatiana; Abramchuk, Olha M.; Kuznietsov, Illya (Східноєвропейський Національний університет імені Лесі Українки, 2015)
Мета роботи полягала у вивченні особливостей джерел викликаної активності кори головного мозку та їх локалізації в лівшів та правшів під час класифікації стимулів, пов’язаних із локалізацією та формою об’єкта. У дослідженні брали участь 33 особи чоловічої статі, віком 18–20 років, які були поділені на дві групи – лівші (14 осіб) та правші (19 осіб). У досліджуваних осіб із лівим типом сенсомоторної асиметрії, незалежно від експериментальної ситуації, найбільш типові джерела електричної активності зафіксовані здебільшого в задньоасоціатівних ділянках лівої півкулі. У правшів розміщення диполів у двох експериментальних ситуаціях менш одноманітне. Так, під час першого тесту найбільш стаціонарні диполі зафіксовані в лівій півкулі, другого – у правій. Our research was aimed at studying evoked activity sources of left- and right-handers, based on ERP ICA-analysis under conditions of adequate perceptive task. 33 males, age 18–20, divided into two groups according to manual asymmetry tests (14 left- handed subjects, 19 right-handed subjects), took part in our study. The experiment consisted of two functional probes, during which the ERPs were registered. During first probe the subjects had to respond to painted figure of specific form among the outlined figures of other forms, regardless of the figure position on the screen. During second probe the subjects had to respond to any painted figure, which was found on the right upper corner of the screen. After getting ERP data, the ICA-analysis was conducted. Artifact and low-significance ICA-components were excluded from further processing. The most typical sources of evoked activity were defined for left- and right-handers. It was shown, that right-handers have more typical electrical activity sources during first probe, herewith one typical source was registered in right superior temporal gyrus. The left-handers had no such typical source, here with, they had 3 of 4 typical sources localized in limbic system structures. During the second probe, each experimental group had 6 typical sources, which were localized mainly in limbic system structures and occipital cortex regions. One of the typical sources in right-handers was localized in right parietal cortex. This was the specific feature of the right-handers group.
Brain Cortex Evoked Activity Sources Features During Stimuli Form and Spatial Position Classification in Groups of Left- and Right-handers.
Keywords: викликані потенціали; правші; лівші; джерело електричної активності; диполь; left-handers; evoked potentials; right-handers; electrical activity source; dipole